Pengaruh Likuiditas, Profitabilitas, Dan Solvabilitas Terhadap Kebijakan Dividen Pada Perusahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Rizkiyeh Rizkiyeh; Bambang Sudarsono (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
Effect of Liquidity, Profitability, and Solvency on Dividend Policy in Automotive Companies Listed on the Indonesia Stock Exchange (IDX) 2016-2020.  Under the guidance of  Drs.  Bambang Sudarsono, MM.This study aims to determine the effect of liquidity, profitability, and solvency variables on dividend policy in automotive companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020.The approach used in this research is quantitative research.  The number of samples in this study were 7 companies.  The data analysis technique used in this research is multiple linear regression analysis, with hypothesis testing statistical t-test and statistical f-test.Based on the research that has been done, the results show that liquidity and profitability have a significant positive effect on dividend policy, while solvency has no effect on dividend policy, but liquidity, profitability and solvency have a simultaneous positive and significant effect on dividend policy.